Short-term arrival strategies for endurance exercise performance at moderate altitude - Foss, J. L.; Constantini, K.; Mickleborough, T. D.; Chapman, R. F. (Journal of Applied Physiology, 2017)
For sea level-based endurance athletes who compete at moderate and high altitudes, many are not logistically able to arrive at altitude weeks before the event to fully acclimatize. For those who can only arrive at altitude the night before competition, we asked if there is a physiological and performance advantage in reducing altitude exposure time to 2 h before competition. On three separate visits, 10 cyclists completed overnight laboratory exposures of: 1) a 14-h exposure to normobaric hypoxia (16.2% O2, simulating 2,500 m; 14H), 2) a 12-h exposure to normoxia, then a 2-h hypoxic exposure (2H), and 3) a 14-h exposure to normoxia (CON). Immediately following each exposure, subjects completed a 20-km cycle ergometry time trial in normoxia (CON) or 16.2% O2 (14H and 2H). Measures of plasma volume changes, sleep quality, ventilatory acclimatization, perceived exertion, oxygen uptake, and 20-km time were collected. No significant differences were observed in performance measures or perceived exertion between hypoxic trials. Plasma volume loss was significantly greater during 14H than 2H and CON. No differences in ventilatory acclimatization or sleep quality were observed between trials. Although some divergent 20-km performance responses were observed between 14H and 2H, they were not explained by the physiological measures completed. The data suggest that endurance athletes who are logistically restricted from arriving at altitude more than the evening before competition would not gain an advantage by delaying their arrival until a few hours before the competition, although unique individual responses may ultimately influence optimal arrival strategy. NEW & NOTEWORTHY For athletes who cannot arrive at altitude multiple days before an endurance competition to properly acclimatize, this study asked if shortening hypoxic exposure time to 2 h before a competition was more advantageous than arrival at altitude the evening before competition. Our data suggest that athletes who cannot arrive at altitude with adequate time for complete acclimatization can choose the short-term arrival strategy that best fits with the logistics of their travel.